Manajemen Keuangan Dalam Meningkatkan Kemandirian Sekolah Di Smp It Pgri Lubuklinggau - Efendi , Syahwan; Connie (Manajer Pendididikan, 2024)
- The purpose of the study was to describe financial management in increasing school independence at SMP IT PGRI Lubuklinggau. The research design used is a qualitative research method using a descriptive approach. The subjects of this study were the principal, treasurer and vice principal of the curriculum. Data collection techniques are done by interview techniques that will be analyzed by data reduction, data presentation and conclusion drawing. The results of the study are 1) Existing budget preparation has been going well although there is still no teacher participation in budget preparation and lack of evaluation of budget implementation. 2) Financial budget bookkeeping is carried out systematically and structured in recording the receipt and expenditure of education funds. 3) Examination of the financial budget in the form of supervision and inspection. Supervision is carried out by the principal while the inspection is carried out from two directions, namely from the school and also from the Financial Audit Agency (BPK) and is carried out once a semester. 4) Funding independence has gone well. SMP IT PGRI Lubuklinggau has optimized funding sources from entrepreneurship and partnership. Funds obtained from Entrepreneurship are canteen rent and school cooperatives. While the Partnership is a voluntary donation of alumni and grant funds from PGRI Lubuklinggau University.